A Functional Model Of Language, Interrelations Of Language, Text And Context, And The Implications For Language Teaching - Baginda Simaibang (LINGUISTIKA, 2011)
The purpose of this research is to explore the interrelations of language, context and text and the implications for language teaching. In this investigation, the children were recorded and their conversations were transcribed. The transcription of the conversation and the language of advertisement were analysed using the Halliday and the Jacobson models of language functions. How the functional model was used in the assessment of texts and how were language, context and text were interrelated will lead us into a linguistic thought that the practical uses of the language could contribute to the teaching and education developments. The results indicated that the children conversations and the language of advertisement do reflect model of language functions. For example; the functions can be identifying, encouraging, offering and requesting. These findings show an understanding that functional model actually contribute to communicative teaching approaches. This is an approach that may be adopted by teachers of foreign language teaching where learners are not exposed to the target language.